Association of melanin content with conidiogenesis and virulence in Bipolaris Sorokiniana - Aggarwal, Rashmi; Banerjee, Sagar; Sharma, Sapna; Gupta, Sangeeta; Bashyal, B M (Journal of Cereal Research, 2011)
B. sorokiniana pathogen has emerged as a serious threat for wheat cultivation in the developing world. Warm and humid environment is conducive for the development of the disease. The information on importance of melanin in spot blotch pathogen B. sorokiniana of wheat and its association with conidiogenesis and virulence is not available. Therefore, studies were undertaken to find whether melanin content of the pathogen is related to conidiogenesis and virulence.